2022
DOI: 10.1039/d1ta06075a
|View full text |Cite
|
Sign up to set email alerts
|

Facet-engineered TiO2 nanomaterials reveal the role of water–oxide interactions in surface protonic conduction

Abstract: Water adsorption and surface protonic conduction have been investigated at 25 – 400 oC in wet (H2O and D2O) atmospheres on nanocrystalline TiO2 hydrothermally grown to a predominance of different...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 46 publications
1
22
1
Order By: Relevance
“…For our monoclinic ZrO 2 samples, however, there is no such secondary increase in conductivity. This is similar to the {101} facet of TiO 2 33 and our on-going work on undoped CeO 2 39 where it even increases less steeply above RHs of 60%. As our data do not extensively explore the region at RH > 60%, we refrain from analysing that region further and it is not part of Table 2.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…For our monoclinic ZrO 2 samples, however, there is no such secondary increase in conductivity. This is similar to the {101} facet of TiO 2 33 and our on-going work on undoped CeO 2 39 where it even increases less steeply above RHs of 60%. As our data do not extensively explore the region at RH > 60%, we refrain from analysing that region further and it is not part of Table 2.…”
Section: Resultssupporting
confidence: 84%
“…, below 50 °C at p H 2 O = 0.03 bar, a 2 nd liquid-like physisorbed layer is expected with strong increase in conductivity as temperature decreases further, as observed for, e.g. , porous YSZ 15 and TiO 2 , 33 but this was not evidenced in this study of monoclinic ZrO 2 .…”
Section: Models and Quantitative Interpretationcontrasting
confidence: 49%
See 2 more Smart Citations
“…8 Relatively few attempts to probe TiO2 surfaces directly in aqueous environments have been reported so far. These included studies by inelastic and quasi-elastic neutron scattering (INS/QENS), [9][10][11] atomic force microscopy (AFM), 12 infrared spectroscopy (IR) 13 and sum frequency generation (SFG). 14 Although these studies indicated the existence of a layer of constrained water molecules with limited mobility at the nanoparticles perimeter, no further insights concerning reactivity could be elucidated.…”
mentioning
confidence: 99%